083 Circadian Preference is Associated with Impulsivity at Both the Trait and State Level. (3rd May 2021) - Hasler, Brant; Wallace, Meredith; Graves, Jessica; Pedersen, Sarah
Abstract: Introduction: Impulsivity is a multifaceted construct with well-documented risk for substance use problems. A circadian preference towards eveningness has been linked to trait, global impulsivity. Here we extend existing literature by investigating whether eveningness is associated with multiple facets of impulsivity at both trait- and state-level impulsivity. We also examined these associations utilizing daily measures of sleep timing and duration. Methods: The primary sample included 78 moderate-to-heavy social drinkers (aged 21–35, 100% White men) with circadian preference data (Composite Scale of Morningness: CSM). Five facets of impulsivity were assessed via the UPPS-P, both at baseline (full scale) and up to 6 times per day over 10 days (reduced scale). Daily sleep timing (midsleep) and duration were assessed via self-report over 10 days. Multilevel models were used to examine between- and within-person associations, accounting for covariates and correcting for multiple comparisons. Results: Between-person models found that eveningness was associated with multiple facets of impulsivity, at trait (lack of perseverance) and state levels (negative urgency, positive urgency, lack of perseverance, and lack of premeditation). However, average midsleep and duration were generally unrelated to impulsivity when accounting for circadian preference. Within-person models in the primary sample largely paralleled the between-person findings. In a larger, more diverse sample (29.1% self-identified as Black, 29.7% female) without CSM data, later midsleep timing was associated with greater mean state-level impulsivity across multiple facets. These effects largely appear to be driven by White women. Conclusion: A circadian preference for eveningness is strongly associated with multiple facets of impulsivity, at both trait- and state-levels, potentially increasing risk for substance use. This association does not appear to be driven by actual daily sleep timing and/or duration. Future research with objective measures of sleep in larger, more diverse samples will be important to clarify implications for sleep-focused prevention and/or treatment of substance use. Support (if any): Supported by grants from NIH (R01AA026249; K01 AA021135), as well as a Foundation Grant from ABMRF/The Foundation for Alcohol Research.